The Importance of External Audit in Detecting Abnormalities and Fraud in the Financial Statements of Public Enterprises in Kosovo - Ismajli, Hysen; Perjuci, Edona; Prenaj, Vlora; Braha, Medina (Ekonomika, 2019)
[full article and abstract in English]This paper focuses on determinants and their impact on the audit of public enterprises in Kosovo. In addition, it analyzes the impact of audit quality on improving the transparency and accountability of those enterprises. The study also assesses factors that affect the effectiveness and ineffectiveness of information in the audit reports of the Kosovo National Audit Office. The data were obtained based on observations, documentation, questionnaires, and interviews. Respondents were internal auditors of public enterprises in Kosovo as well as external auditors of the Kosovo National Audit Office. This research was designed using primary and secondary sources of data and was carried out in accordance with statistical analysis methods using the average algebraic size method and absolute variation indicators.The findings of this paper suggest that external auditors consider the potential risk of errors and fraud as being high, that they have aversive attitudes against errors and fraud, and that there exists for them a negative relationship between errors, fraud and financial reporting. Also, the quality of external audit positively affects the detection of fraud and anomalies within financial statements.
Keywords: Kosovo